Classroom Guidance Strategy with Flipped Method in Guidance and Counseling Services at Indonesia Schools in the Digital Era: Array - Mulawarman Mulawarman; Susilawati Susilawati; Layyinatus Syifa; Endang Rifani (Islamic Guidance and Counseling Journal, 2020)
The demand for a better education system will result in not only a better academic achievement but also students with better character. Particularly in this digital era, it is very important to integrate technology in the process of guidance and counseling services at schools. This article aims to provide a critical review of implementation and application of classical guidance with format flipped classroom in coping with the advance of technology as an effort that can be made by school counselors in order to make innovation in guidance and counseling service at schools. This research method is a literature study. This study collected and analyzed relevant journals related to the use of flipped classroom. Class guidance with flipped classroom format has the potential to help school counselors to manage classical guidance and stimulate students to be active, communicative, and contributive to the process of guidance so that the topic presented can be addressed directly. In addition, by doing this, it is expected that students can develop themselves well in their social, academic, and career life. School counselors can use flipped classroom guidance to make innovation in performing classroom guidance services. The steps to perform flipped classroom guidance, in brief, are determine the topic to be discussed based on the need of the student, creating service program plan, then setting up the activities that the students will do in pre-class activity and inside the class, the implementation of the activities and evaluation, and follow up.